Forest drainage effects on tree growth in Northern Sweden - Glöd, Hanna (2019)
At present, there are no clear guidelines for when and where ditch network maintenance (DNM) should be performed in Sweden. Recently there have been attempts to create tools that indicate the need for DNM, one of these tools is the Ditch Flow Tracker (DFT). The DFT determines the catchment area (CA) and soil type to predict if a ditch segment does not need DNM. The tool is based on the hypothesis that ditches with small CA’s do not need maintenance because they do not function to drain enough water to improve tree growth. The overall goal of this study was to ground truth the DFT by testing how well the CA, soil type and water flow divided into category can predict ditch function in terms of tree growth. Since the decision of DNM should take into account the ecological impacts the ability of the DFT to predict biodiversity of plants was also tested.